Adult Vaccination in the United Arab Emirates—A Physicians' Knowledge and Knowledge Sources Study - Barqawi, Hiba J.; Samara, Kamel A.; Hassan, Mahmoud S.; Amawi, Firas B. (Frontiers in Public Health, 2022)
Background A lack of knowledge on adult vaccination has been documented among physicians. They play a critical role in promoting adult vaccines. This study aimed to review the status of adult vaccination in the United Arab Emirates (UAE) and evaluate physicians' knowledge and knowledge sources regarding adult vaccines. Methods Local, regional, and global adult vaccination guidelines were reviewed. A 40-item questionnaire was used to collect data from physicians from June to October 2020, using convenience and snowball sampling. Knowledge score was calculated, and predictors identified using Mann–Whitney U and Kruskal–Wallis H-tests. Ordinary Least Squares regression was used for Multivariate Analysis. Results A total of 500 responses were included. A quarter were internists, and another quarter were family physicians. Fifty-seven percent were medical interns and residents. Both perceived and actual knowledge of adult vaccination were low. Bivariate analysis showed knowledge depending on department, level of training, workplace, and perceived knowledge. All remained significant after multivariable regression except workplace. International and local guidelines were the most common knowledge sources. Forty-two percent were unable to access the local guidelines. Conclusions Physicians' knowledge was poor and local guidelines were not clear or easily accessible. Participants were highly receptive to guidance and practice with adult vaccines.